Pelatihan Mindfulness-Based Stress Reduction untuk Menurunkan Stres pada Wanita Relawan Satgas DIY - Ike Nirta Sari; Kamsih Astuti (Lembaga Pengembangan Kinerja Dosen, 2025)
The participation of women today is not limited to demanding equal rights, but also demonstrating their functional significance in contributing to societal development in Indonesia. This study aims to examine the influence of training Mindfulness-based stress reduction on stress levels among female task force members in the Special Region of Yogyakarta. The research employed a non-equivalent control group design. The participants consisted of 10 women assigned to the Yogyakarta task force, divided into two groups: an experimental group and a control group. The experimental group received an intervention in the form of Mindfulness-Based Stress Reduction, while the control group received no intervention. The instrument used to measure stress levels was the Perceived Stress Scale-10, which had a reliability of 0.83. Data were analyzed using the Mann-Whitney U test and the Wilcoxon Signed-Rank test. The results indicated a significant difference in stress levels between the experimental group and the control group, with Z = -2.627 and p = 0.009 (p < 0.005). Additionally, there was a significant difference in stress scores within the experimental group before and after the MBSR intervention, with Z = -2.041 and p = 0.041 (p < 0.05). These findings suggest that Mindfulness-Based Stress Reduction has a significant effect in reducing stress levels among female task force members in the Special Region of Yogyakarta, thereby helping them to manage their stress more effectively in daily life.